Anthrax prophylaxis: recent advances and future directions - Williamson, Diane; Dyson, Edward H. (Frontiers in Microbiology, 2015)
Anthrax is a serious, potentially fatal disease that can present in four distinct clinical patterns depending on the route of infection (cutaneous, gastrointestinal, pneumonic or injectional), so that effective strategies for prophylaxis and therapy are therefore required. Anthrax is a serious disease, requiring effective strategies for prophylaxis and therapy. This review addresses the complex mechanisms of pathogenesis employed by the bacterium and describes how, as understanding of these has developed over many years, so too have current strategies for vaccination and therapy. It covers the clinical and veterinary use of live attenuated strains of anthrax and the subsequent identification of protein sub-units for incorporation into vaccines, as well as combinations of protein sub-units with spore or other components. It also addresses the application of these vaccines for conventional prophylactic use, as well as post-exposure use in conjunction with antibiotics. It describes the licensed acellular vaccines AVA and AVP and discusses the prospects for a next generation of recombinant sub-unit vaccines for anthrax, balancing the regulatory requirement and current drive for highly defined vaccines, against the risk of losing the ‘danger’ signals required to induced protective immunity in the vaccinee. It considers novel approaches to reduce time to immunity by means of combining, for example, dendritic cell vaccination with conventional approaches and considers current opportunities for the immunotherapy of anthrax.